The determinants of foreign investment size: the role of parent firm advantage and cross-national distance. (23rd January 2023) - Zhou, Nan; Hu, Tianyou; Delios, Andrew
This study investigates the determinants of foreign investment size by considering the role of both parent firm advantage and cross-national distance. We first develop an economic model of foreign investment size. Building on this model and theories in international business, we derive hypotheses on the determinants of foreign investment size: it is positively related to parent firm-specific advantage, while it follows an inverted U-shape relationship with different dimensions of cross-national distances. Moreover, parent firm advantage and cross-national distance interact with each other to influence investment size. Our empirical analysis of Japanese firms' foreign direct investment (FDI) data from 1990 to 2009 supports our hypotheses. Our study contributes to the literature on FDI by examining an overlooked aspect of FDI: investment size. We also integrate economic model and international business theories to explain firm-level and country-level determinants of foreign investment size.